A high-efficiency solar cell prepared using ultra-low concentration aqueous solution and preparation method thereof

By using ultra-low concentration aqueous solution to prepare the electron transport layer, the problems of high energy consumption, high process complexity and inability to adapt to thin silicon wafers in the prior art are solved, and efficient and low-cost crystalline silicon solar cell preparation is achieved, and the material is safe and non-toxic.

CN115274920BActive Publication Date: 2025-04-15SUN YAT SEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210806722.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-08
Publication Date
2025-04-15
Estimated Expiration
2042-07-08

AI Technical Summary

Technical Problem

The existing crystalline silicon solar cell technology has problems such as high energy consumption, high process complexity and inability to adapt to thin silicon wafers. The electron transport layer prepared by the solution method has poor stability and complex film formation, and toxic surfactants are often required.

Method used

An ultra-low concentration aqueous solution is used to prepare an electron transport layer. The active ingredients of the solution are selected from Lewis acid, neutral surfactant, ionic surfactant or laundry detergent, with a concentration of 0.5-15 mg/mL. A uniformly dispersed system is formed by oscillation or ultrasound, and then a film is formed by spin coating or lifting method.

Benefits of technology

It realizes efficient solar cell preparation without high-temperature doping process, low-cost, and compatible with thin silicon wafers. The production process of the electronic transport layer is simple, the material is safe and non-toxic, which significantly reduces the energy consumption and cost of battery preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115274920B_ABST
    Figure CN115274920B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of crystalline silicon photovoltaic cells, and specifically relates to a high-efficiency solar cell prepared using an ultra-low concentration aqueous solution and a preparation method thereof. The present invention uses an ultra-low concentration aqueous solution to prepare the electron transport layer of the solar cell. The preparation method is extremely simple, does not require expensive PECVD equipment and a high-temperature diffusion furnace, is prepared based on a low-temperature process, has a relatively low cost, is compatible with thin silicon wafers, and has an outstanding cost reduction effect; at the same time, the electron transport layer does not require doping, the process is greatly simplified, does not contain irritating organic solvents such as methanol and acetone, and is environmentally friendly and safe; the main active ingredient of the aqueous solution used is a surfactant, and the range of materials available is wider, including previously reported Lewis acids and neutral surfactants, ionic surfactants, etc., and can even be extremely common laundry detergent. In addition, the electron transport side electrode in the crystalline silicon solar cell of the present invention can be directly made of aluminum, which can achieve lower costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crystalline silicon photovoltaic cells, and in particular relates to a high-efficiency solar cell prepared by using an ultra-low concentration aqueous solution and a preparation method thereof. Background Art

[0002] Efficient and low-cost photovoltaic cells are of great significance for reducing the cost of new energy electricity and accelerating the realization of global carbon neutrality goals.

[0003] At present, mainstream battery technologies are all based on high-temperature passivation contacts, such as emitter and back passivation cell (PERC) technology and tunneling oxide passivation contact (TOPCon) cell technology. However, since the hole transport layer and electron transport layer of this technology are completed based on high-temperature (>800℃) doping process, there will be problems such as high energy consumption, complex process, and unsuitability for thin silicon wafers. The typical low-temperature (<450℃) passivation contact technology is silicon heterojunction cell (also known as HJT / HDT / HIT / SHJ) technology. Although this technology avoids high temperature and is compatible with thin silicon wafers, its electron and hole transport layers still cannot do without heavy doping, which has the disadvantages of large parasitic absorption, narrow process window, relatively complex process, and the need for special low-temperature silver paste.

[0004] At present, although there have been some reports on the preparation of silicon solar cells using the solution method, they are mainly based on the hole end, such as PEDOT:PSS or CuSCN. These materials have poor stability, and in order to maintain good film-forming properties, some surfactants or organic solvents need to be added to the high-concentration solution. The solution composition is complex and the repeatability is poor. At the same time, there are also reports on the preparation of electron transport layers based on the solution method, such as PEI / PEIE, Cs 2 CO 3 +PEI, methanol solution of metal acetylacetonate, etc., but the solution used is limited to the solution of Lewis acid, and the concentration is high, often containing toxic components. Therefore, it is necessary to develop a new type of crystalline silicon solar cell to solve the above technical problems. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings of the prior art, the primary purpose of the present invention is to provide a method for preparing high-efficiency solar cells using ultra-low concentration aqueous solutions. The method does not require expensive coating equipment, the thickness is easy to control, does not rely on high-temperature diffusion and dangerous gas source doping, and the preparation cost is relatively low.

[0006] The second object of the present invention is to provide a solar cell prepared by the above method. The electron transport layer of the cell is made based on an ultra-low concentration aqueous solution, thereby reducing the cost of cell preparation.

[0007] The first invention objective of the present invention is achieved through the following technical solutions:

[0008] The present invention provides a method for preparing a high-efficiency solar cell by using an ultra-low concentration aqueous solution. When preparing the solar cell, an ultra-low concentration aqueous solution is used to prepare an electron transport layer. The active ingredient of the aqueous solution is selected from at least one of Lewis acid, neutral surfactant, ionic surfactant and washing powder. The concentration of the aqueous solution is 0.5-15 mg / mL.

[0009] The solution used in the present invention has simple composition and is relatively safe and non-toxic (ultra-low concentration aqueous solution). At the same time, the materials used are more universal and can be extended to almost all aqueous solutions of surfactants rather than just aqueous solutions of Lewis acids. The raw materials are more abundant and the preparation cost is lower.

[0010] The core of the present invention is to form an undoped electron transport layer based on an ultra-low concentration aqueous solution, eliminating high temperature and complex doping processes. After preparing this film, covering it with a metal electrode can achieve good electron selectivity and high efficiency, which can greatly reduce the preparation cost of the battery. The electron transport layer is made based on an ultra-low concentration aqueous solution, without deliberate doping, and has a thickness of 0.5-5nm. The concentration of the aqueous solution is not higher than 15mg / mL, and the main active ingredient is a surfactant, etc. It has the effect of conducting electrons with low resistance and blocking hole conduction, and is used to achieve selective extraction of electronic current in the battery.

[0011] Preferably, the active ingredient of the aqueous solution is selected from Triton or washing powder.

[0012] Preferably, the thickness of the electron transport layer is 0.5-5 nm. The preparation method of the electron transport layer is: preparing an aqueous solution containing an active ingredient (such as a surfactant) with a concentration of 0.5-15 mg / mL, and forming a uniformly dispersed system by oscillation or ultrasound, and then forming a film on the substrate surface by spin coating or pulling method, and the final film thickness formed is 0.5-5 nm.

[0013] More preferably, the electron transport layer is disposed on the back side of the battery.

[0014] More preferably, a passivation film is first prepared on the back of the battery, and then an electron transport layer is prepared on the surface of the passivation film, and the thickness of the passivation film is 1-2 nm. The passivation film can be formed by high temperature thermal oxidation or HNO 3 Silicon oxide prepared by oxidation or even low-temperature annealing in an oxygen-containing atmosphere, ozone treatment, etc., can also be intrinsic hydrogenated amorphous silicon prepared by methods such as PECVD, and aluminum oxide and titanium oxide prepared by ALD technology. Its function is to reduce the dangling bonds on the surface of the silicon wafer and eliminate the Fermi pinning effect of the interface. The thickness of the passivation film is generally about 1.5nm.

[0015] Preferably, a metal electrode is disposed on the surface of the electron transport layer, and the metal electrode includes an aluminum electrode. The electrode of the present invention is preferably an aluminum electrode, and the deposition method can be thermal evaporation, magnetron sputtering or screen printing, with a thickness of ≥300nm.

[0016] More preferably, in order to improve the battery efficiency, a metal halide or a low work function metal structure is further provided between the electron transport layer and the metal electrode. The metal halide includes lithium fluoride, cesium fluoride, ytterbium fluoride, sodium chloride, cesium iodide, etc. The metal with low work function includes Li, Ba, Ca, Mg, Yb, Sc, etc.

[0017] The second invention objective of the present invention is achieved through the following technical solutions:

[0018] The invention also provides a solar cell prepared by the preparation method.

[0019] The solar cell of the present invention has an electron transport layer made of an ultra-low concentration aqueous solution through a spin coating process or a pulling process, without the need for doping, and then directly covers a metal aluminum electrode to achieve good electron selective transport. The production process of the battery's electron transport layer is simple, the raw materials are cheap and easily available, safe and non-toxic, and can greatly reduce the energy consumption of battery preparation and the battery cost.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention discloses a high-efficiency solar cell structure prepared by ultra-low concentration aqueous solution. The preparation method of the electron transport layer in the crystalline silicon solar cell is extremely simple, does not require expensive PECVD equipment and high-temperature diffusion furnace, is prepared based on a low-temperature (<450°C) process, has relatively low cost, is compatible with thin silicon wafers, and has outstanding cost reduction effects; at the same time, the electron transport layer used in the present invention does not require doping, and the process is greatly simplified; the electron transport layer used in the present invention is prepared based on an ultra-low concentration aqueous solution, does not contain irritating organic solvents such as methanol and acetone, and the material is environmentally friendly and safe; the main active ingredient of the aqueous solution used in the present invention is a surfactant, and the material selection range is wider, including previously reported Lewis acids and neutral surfactants, ionic surfactants, etc., and can even be extremely common laundry detergent. In addition, the electron transport side electrode in the crystalline silicon solar cell of the present invention can be directly made of aluminum, which can achieve lower costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the solar cell structure with an electron transport layer made from ultra-low concentration aqueous solution;

[0023] Figure 1In the figure, 1 is an n-type silicon wafer, 2 and 6 are a-Si:H(i), 3 is a-Si:H(p), 4 is ITO, 5 is a silver electrode, 7 is an electron transport layer, and 8 is an aluminum electrode.

[0024] Figure 2 The change of contact resistivity between the electron transport layer and n-Si made of different concentrations of Triton aqueous solution;

[0025] Figure 3 The contact between the electron transport layer made of Triton aqueous solution and n-Si when covering different metal electrodes;

[0026] Figure 4 The IV curves of a crystalline silicon solar cell using a Triton aqueous solution to make an electron transport layer and a solar cell without such an electron transport layer are compared. DETAILED DESCRIPTION

[0027] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0028] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0029] Example 1 Effect of different concentrations of aqueous solution on electron selective contact effect

[0030] (1) Preparation of ultra-low concentration aqueous solution: Use water as the only solvent to prepare a Triton X-100 aqueous solution with a concentration of 0.5-20.2 mg / mL. Ultrasonicate the solution in an ultrasonic cleaner for 3 min at room temperature to form a uniformly dispersed solution. The solution also needs to be ultrasonicated for 3 min before each use.

[0031] (2) Silicon wafer texturing and cleaning: Use n-type silicon wafer with a resistivity of 1-3Ω·cm as the substrate. First, soak the silicon wafer in a 20% KOH or NaOH aqueous solution at 75-80°C for 2-10 minutes to remove the cutting damage layer on the surface of the silicon wafer. Then, soak it in a mixed solution containing 3% (mass percentage) potassium hydroxide KOH and 4.5% (volume percentage) isopropyl alcohol IPA at 50°C for 20 minutes to form a pyramid structure on the surface of the silicon wafer to reduce optical reflection loss.

[0032] After texturing, the silicon wafer is then cleaned. During cleaning, the organic matter is removed first, then the oxide film, and then the metal is removed. The silicon wafer is treated with the following solutions in order to remove various contaminants that may exist on the surface of the silicon wafer to obtain a clean surface:

[0033] ① By H 2 SO 4 (mass fraction 98%) and H 2 O 2 (mass fraction 30%) is composed of SPM in a volume fraction of 3:1, heated to a temperature of 120-150°C, and the soaking time is 10 minutes; this solution can strongly remove organic contamination on the surface of the silicon wafer. After the silicon wafer is taken out of the solution, it is immediately placed in deionized water at a temperature of 80°C and soaked for 2 minutes, then taken out and rinsed with a large amount of deionized water to remove the acid that may remain on the surface. The SPM solution can also be replaced with deionized water containing ozone.

[0034] ② By NH 4 OH (mass fraction 28%), H 2 O 2 (mass fraction 30%) and H 2 O (18.2MΩ·cm deionized water) is used to form an SC-1 solution in a volume fraction of 1:1:5, heated to a temperature of 75-85°C, and the soaking time is 10 minutes; then the silicon wafer is taken out and the alkali solution remaining on the surface is rinsed off with a large amount of deionized water.

[0035] ③ HCl (mass fraction 37%), H 2 O 2 (mass fraction 30%) and H 2 O (18.2MΩ·cm deionized water) is used to form an SC-2 solution in a volume fraction of 1:1:5, heated to a temperature of 75-85°C, and the soaking time is 10 minutes; then the silicon wafer is taken out and the acid remaining on the surface is rinsed off with a large amount of deionized water.

[0036] ④ HF (mass fraction 37%) and H 2 O (18.2MΩ·cm deionized water) is used to form a DHF solution with a volume fraction of 1:99, at room temperature, and the immersion time is 10s; then the silicon wafer is taken out and immersed in deionized water, and then taken out and the residual moisture on the surface of the silicon wafer is blown dry with nitrogen.

[0037] (3) Preparation of undoped electron transport layer film (and passivation film): The cleaned and textured silicon wafer is adsorbed on a spin coater, and 60 μL of the Triton aqueous solution prepared in step (1) is taken with a pipette and dropped on the center of the silicon wafer and spread fully; then, the film is spin-coated at a low speed (1000 rpm) for 15 s, and then at a high speed (4000 rpm) for 60 s. The silicon wafer is then taken out and placed on a heating table at 60°C and heated in air for 5 min to accelerate the volatilization of residual water in the film and form a natural oxide layer at the interface as an interface passivation film.

[0038] (4) Aluminum electrode preparation: Aluminum wire is used as the evaporation source and wound around tungsten wire to form a spiral structure. The cavity reaches (4-8)×10 -4 Pa (5×10 -4 Pa) and then a DC power supply is used to heat the tungsten wire loaded with aluminum wire. The substrate does not need to be heated, and the film growth rate is The thickness of the film finally formed was 350 nm.

[0039] As a control, a 20 nm thick gold film can also be inserted in front of the aluminum electrode to test the mechanism of action of Triton: two gold particles are placed in a quartz crucible, and then the coating chamber of the thermal evaporation coating machine reaches (4-8)×10 -4 Pa (5×10 -4 Pa) of background vacuum, a DC power supply is used to heat the crucible loaded with gold particles, and the substrate does not need to be heated. The film growth rate is The thickness of the final gold film was 20 nm.

[0040] After the above four steps, a highly efficient electron selective contact can be prepared on n-Si with a Triton X-100 film as an undoped electron transport layer and natural silicon oxide as an interface passivation layer. The process temperature of all steps does not exceed 450°C, so it is a typical low-temperature process.

[0041] Figure 2 The contact resistivity of different concentrations of Triton X-100 aqueous solution and n-Si is shown in Figure 2. It can be seen that when the concentration of Triton X-100 is 0.5-10 mg / mL, the contact resistivity is small (<0.1Ω·cm 2 ), which can meet the performance requirements of crystalline silicon solar cells.

[0042] Figure 3The corresponding contact conditions when n-Si / Qulatin uses Au / Al and Al alone as electrodes. From the current range of the horizontal axis, it can be seen that the effect of the Qulatin film when used with Au / Al electrodes is far worse than that of the Al electrode alone, indicating that relying solely on the Qulatin film itself cannot achieve a sufficiently good resistance selective contact. The role of the Qulatin film is to use the insulating properties to reduce the defect states (MIGS) generated by the metal electrode in the band gap of the narrow bandgap semiconductor (here n-Si), thereby alleviating the Fermi level pinning, so that the work function of the back-end metal can play a role in regulating the band bending. This shows that the mechanism of action of this type of electron transport layer is not dependent on high-density fixed charges or strong dipole effects, but because the material has a wide bandgap that can effectively attenuate the density of inter-band defect states (MIGS) induced by the metal's electronic wave function in the semiconductor, so that the work function of the metal itself can play a role.

[0043] Example 2 Crystalline silicon solar cell based on ultra-low concentration aqueous solution and its preparation

[0044] like Figure 1 As shown, an n-type silicon wafer is used as a substrate, and the back side of the substrate includes a back passivation film a-Si:H(i), an electron transport layer (Qulatan film) and an aluminum electrode (negative electrode) from the inside to the outside, and the front side of the substrate includes a front passivation film a-Si:H(i), a-Si:H(p), ITO and a silver electrode (positive electrode) from the inside to the outside, and the silver electrode is used to conduct and collect holes.

[0045] The preparation of the crystalline silicon solar cell comprises the following steps:

[0046] 1. Preparation method of the positive side of the battery:

[0047] (1) Texturing and cleaning: The specific method is the same as step (2) of Example 1.

[0048] (2) Preparation of intrinsic hydrogenated amorphous silicon thin film (passivation film) a-Si:H(i): 4 and H 2 The flow ratio is 1:5, the substrate temperature is 200°C, the deposition pressure is 20Pa, and the plate power density is 0.05W / cm 2 Under the conditions of , PECVD is used to deposit a 4-6nm intrinsic amorphous silicon film (5nm in this embodiment) on the velvet surface.

[0049] (3) Preparation of n-type doped amorphous silicon film (hole transport layer) a-Si:H(p): 4 :H 2 :PH 3The flow ratio is 2:45:1, the substrate temperature is 180°C, the deposition pressure is 35Pa, and the plate power density is 0.1W / cm 2 Under the conditions of , PECVD is used to deposit a 3-6nm n-type doped amorphous silicon film (4nm in this embodiment) on the intrinsic amorphous silicon film.

[0050] (4) Preparation of ITO film: The ITO film was deposited on the n-type doped amorphous silicon film by magnetron sputtering. In an argon atmosphere, a DC RF power supply was used at a pressure of 0.35-0.4 Pa, a power of 100 W, a DC bias of 150 V, and a deposition rate of Under the conditions of , a 70-80nm ITO film (75nm in this embodiment) is deposited.

[0051] (5) Preparation of front electrode (silver electrode): After attaching a mask to the surface of the ITO film, place it in a thermal evaporation coating machine to evaporate the silver electrode. The substrate is not heated and the vacuum degree is 4×10 -4 Pa, the evaporation rate is The thickness is 1200nm. Then the battery is placed on a heating table at 200℃ in air for 1h to strengthen the contact.

[0052] 2. Preparation of the back of the battery

[0053] (1) Preparation of passivation film a-Si:H(i) and electron transport layer: The silicon wafer with the front surface was adsorbed on a spin coater, and 60 μL of a Triton aqueous solution (10.1 mg / mL) was taken up with a pipette and dropped onto the center of the silicon wafer and allowed to spread fully. The wafer was then spin-coated at a low speed (1000 rpm) for 15 s and then at a high speed (4000 rpm) for 60 s. The silicon wafer was then taken out and placed on a heating table at 60°C and heated in air for 5 min to accelerate the volatilization of residual water in the film and form a natural oxide layer at the interface as an interface passivation film.

[0054] (2) The back aluminum electrode is prepared by thermal evaporation: an aluminum wire is used as the evaporation source, which is wound around a tungsten wire to form a spiral structure. The cavity reaches (4-8)×10 -4 Pa (5×10 -4 Pa) and then a DC power supply is used to heat the tungsten wire loaded with aluminum wire. The substrate does not need to be heated, and the film growth rate is The thickness of the film finally formed was 350 nm.

[0055] In addition, a crystalline silicon solar cell without a Triton electron transport layer was used as a control.

[0056] Figure 4This is the IV curve of a crystalline silicon solar cell. It can be seen that if the Triton film is not used as the electron transport layer, the efficiency of the cell is poor, only 7.3%. After using Triton as the electron transport layer, the cell efficiency is significantly improved to 20.4%, and the short-circuit current density is increased by 0.7 mA / cm 2 This indicates that the solar cell prepared by the method of the present invention has a higher photoelectric conversion efficiency.

[0057] Example 3 Crystalline silicon solar cell based on ultra-low concentration aqueous solution and its preparation

[0058] The structure and preparation method of the crystalline silicon solar cell are substantially the same as those of Example 1, except that the electron transport layer is prepared by spin coating a washing powder aqueous solution with a concentration of 4 mg / mL.

[0059] After using laundry detergent as the electron transport layer, the battery efficiency was also significantly improved to 19.82%.

[0060] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing high-efficiency solar cells using ultra-low concentration aqueous solution, characterized in that: When preparing crystalline silicon solar cells, an ultra-low concentration aqueous solution is used to prepare an electron transport layer, the active ingredient of the aqueous solution is selected from Triton, and the concentration of the aqueous solution is 0.5-15 mg / mL.

2. The method for preparing high-efficiency solar cells using ultra-low concentration aqueous solution according to claim 1, characterized in that: The thickness of the electron transport layer is 0.5-5 nm.

3. The method for preparing high-efficiency solar cells using ultra-low concentration aqueous solution according to claim 2, characterized in that: The electron transport layer is arranged on the back side of the battery.

4. The method for preparing high-efficiency solar cells using ultra-low concentration aqueous solution according to claim 3, characterized in that: A passivation film is first prepared on the back of the battery, and then an electron transport layer is prepared on the surface of the passivation film.

5. The method for preparing high-efficiency solar cells using ultra-low concentration aqueous solution according to claim 1, characterized in that: A metal electrode is disposed on the surface of the electron transport layer, and the metal electrode comprises an aluminum electrode.

6. The method for preparing high-efficiency solar cells using ultra-low concentration aqueous solution according to claim 5, characterized in that: A metal halide or a low work function metal structure is also arranged between the electron transport layer and the metal electrode.

7. A crystalline silicon solar cell prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of transparent conductive material of HJT solar cell

    CN109728108A

  • Solar cell and method of manufacturing the same

    JP2016051891A